PELATIHAN TERAPI AKUPRESUR UNTUK MENGATASI KELUHAN PENYAKIT DM DAN HIPERTENSI PADA LANSIA BAGI KADER LANSIA - I Made Mertha; I Ketut Suardana; I Gede Widnjanegara; IGK Gede Ngurah (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
AbstractIncreased prevalence of the elderly will have an impact on health development. This is because in the elderly there is a physiological decline in all body systems, which results in various health problems in the elderly. The main health problems generally experienced by the elderly are hypertension and DM. One program to prevent and control complaints due to DM and hypertension is to do primary prevention with acupressure therapy. Acupressure therapy is one of the therapies that can be done easily that is obtained through training. Training is provided with the aim of comparing the behavior (knowledge, attitudes and skills) of elderly cadres about acupressure therapy before and after training. Community service is carried out through lecture, discussion and acupressure practices. Based on community service that has been done, it can be concluded that the target is mostly in the age group of 40-50 years, 30 people (60%), and most of the female sex is 45 people (90%), target knowledge increases based on good knowledge categories from 20 people (40%) to 35 people (70%), and an increase in attitudes with a very good category from 17 people (34%) to 38 people (76%). For the target audience it is recommended to maintain and improve behavior in acupressure and apply it every day, so as to overcome complaints of hypertension and DM in the elderly during the implementation of the elderly posyandu.Keywords: Elderly; Acupressure; Hypertension; DM.